2018
DOI: 10.1111/1365-2478.12626
|View full text |Cite
|
Sign up to set email alerts
|

Slowness domain offset and traveltime approximations in layered vertical transversely isotropic media

Abstract: Considering horizontally layered transversely isotropic media with vertical symmetry axis and all types of pure‐mode and converted waves we present a new wide‐angle series approximation for the kinematical characteristics of reflected waves: horizontal offset, intercept time, and total reflection traveltime as functions of horizontal slowness. The method is based on combining (gluing) both zero‐offset and (large) finite‐offset series coefficients. The horizontal slowness is bounded by the critical value, chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These results coincide completely with the relationships obtained for VTI in the slowness domain by Koren and Ravve (2018). For an elliptic VTI medium, ε = δ, the second-order coefficients simplify to M 2,P = 1 + 2δ , M 2,SV = 1 , M 2,S H = 1 + 2γ, (C21)…”
supporting
confidence: 79%
See 3 more Smart Citations
“…These results coincide completely with the relationships obtained for VTI in the slowness domain by Koren and Ravve (2018). For an elliptic VTI medium, ε = δ, the second-order coefficients simplify to M 2,P = 1 + 2δ , M 2,SV = 1 , M 2,S H = 1 + 2γ, (C21)…”
supporting
confidence: 79%
“…Starting with an original approximation function for the radial offset, we suggest an approximation function similar to the one applied in the VTI case (Koren and Ravve 2018), where the coefficients A, B, C, D, E are now azimuthally dependent. These coefficients have units of distance, and the radial offset is given by where, again,p h is the normalized slowness andq is the normalized complementary slowness.…”
Section: A P P R O X I M a T I O N S F O R T H E K I N E M A T I C A mentioning
confidence: 99%
See 2 more Smart Citations
“…The P-and SV-waves polarized in the vertical symmetry planes have kinematics defined by four parameters: the vertical P-and S-waves phase velocities and two anisotropy parameters ε and δ (Thomsen 1986). Various moveout approximations have been proposed for VTI media (Stovas 2010;Ravve and Koren 2017;Koren and Ravve 2018). However, it was found that the P-wave moveout is weakly dependent on vertical S-wave phase velocity for practical weakly anelliptic VTI media (Tsvankin and Thomsen 1994;Alkhalifah and Tsvankin 1995).…”
Section: Introductionmentioning
confidence: 99%